Antioxidant Activity of Isolated Bioactive Compound from Mollugo nudicaulis (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Mollugo nudicaulis (M. nudicaulis), a medicinal plant with long history of use in traditional medicine. In the present study focused to explore the in vitro antioxidant potential of 12-(10-carboxydecanoyloxy)-12-oxododecanoic acid (compound-1) isolated and characterized as a specific natural compound from the aerial parts of M. nudicaulis. The results of these in vitro antioxidant assays were promising. Compound-1 demonstrated significant antioxidant activity when compared to the standard drug across all tests, effectively scavenging free radicals. These findings suggest that compound-1 from M. nudicaulis has considerable potential as a natural antioxidant. Its effectiveness indicates that it could be valuable in various applications within the pharmaceutical and food industries. The natural antioxidant properties of compound-1 could contribute to the development of new therapies and preservation methods, providing a natural alternative to synthetic antioxidants. However, to fully understand the potential of compound-1, further studies are necessary. These future investigations should aim to elucidate the precise mechanisms by which compound-1 exerts its antioxidant effects and explore its broader therapeutic applications. Overall, this study highlights the promising pharmacological potential of M. nudicaulis, particularly in the realm of natural antioxidants.